(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the role of numerals in Uzbek phraseological units, as well as their quantitative and qualitative indicators. During the research, it is proven that numbers are not just mathematical units, but a linguistic code that enhances the emotional-expressive coloring of language and expresses the cultural and historical views of a people. The article focuses on the semantic transformation of numerals such as "one," "two," "seven," and "forty" within phraseological units.